2013
DOI: 10.1165/rcmb.2013-0089oc
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2B Receptor and Hyaluronan Modulate Pulmonary Hypertension Associated with Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death worldwide. The development of pulmonary hypertension (PH) in patients with COPD is strongly associated with increased mortality. Chronic inflammation and changes to the lung extracellular matrix (ECM) have been implicated in the pathogenesis of COPD, yet the mechanisms that lead to PH secondary to COPD remain unknown. Our experiments using human lung tissue show increased expression levels of the adenosine A 2B receptor (ADORA2B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 51 publications
13
57
0
Order By: Relevance
“…The reductions in markers for AAM were linked to reduced fibrotic deposition and improved lung function, consistent with studies in mice lacking arginase‐1 in hematopoietic cells where improved lung function following allergen challenge was reported (42). We also demonstrate that mice lacking the ADORA2B in the myeloid cell lineage were protected from the development of PH secondary to lung fibrosis (12), implicating further the role of AAM in the development of lung fibrosis and PH.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The reductions in markers for AAM were linked to reduced fibrotic deposition and improved lung function, consistent with studies in mice lacking arginase‐1 in hematopoietic cells where improved lung function following allergen challenge was reported (42). We also demonstrate that mice lacking the ADORA2B in the myeloid cell lineage were protected from the development of PH secondary to lung fibrosis (12), implicating further the role of AAM in the development of lung fibrosis and PH.…”
Section: Discussionsupporting
confidence: 53%
“…Heightened levels of adenosine have been observed in several chronic lung diseases (11) and in experimental models of PH secondary to chronic lung disease (12, 13, 32). In line with this, we describe accumulation of adenosine in BALF during the progression of fibrosis, reaching a peak on day 33 that is attenuated in BLM‐exposed Adora2B f/f ‐LysM Cre mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA levels were significantly higher in patients with COPD than in those from controls [187189]. Some reports showed that HA levels were decreased in COPD [190] and in COPD with alpha-1 antiprotease deficiency [191].…”
Section: Hyaluronan In Human Diseasesmentioning
confidence: 99%
“…Studies in A 2B receptor knockout mice showed inhibition of the infiltration of neutrophils into tissues under hypoxic conditions [26,27]. Pro-inflammatory effects of A 2B receptors have been seen in murine lung inflammation models and in patients with asthma or chronic obstructive pulmonary disease, suggesting the potential therapeutic value of targeting A 2B receptors as an anti-inflammation measure to prevent the progression of these diseases [28,29]. It has been reported that the A 2B receptor may promote the expression and release of the inflammatory factor IL-6 by vascular endothelial cells in diabetes [12].…”
Section: Discussionmentioning
confidence: 99%